Pendampingan Pendidikan Ahklak dan Kegiatan Sehari-hari di Pondok Pesantren Hidayatul Mustaqim Bulusari Tarokan Kediri - Jumanto; Abd Majid Abror (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Pondok pesantren Hidayatul Mustaqim was established in the early 1970s, the learning system at that time still uses the salaf model, then began to change to the madrasah system in the early 1990s. Then in 2010 it officially gained official recognition from the Ministry of Religious Affairs as an official institution. In general, the process of Ahklak education and daily activities at Pondok Pesantren Hidayatul Mustaqim Bulusari Tarokan Kediri. This can be said to work. The process that in writing only lasted one month indirectly really played a role in helping Pesantren as an institution that really maintains daily activities in pesantren that are increasingly sidelined by outside cultures that are very concerning. Communication and cooperation with pesantren institutions also went well during the research process. The success of this research process can also be a personal motivation for the author so that in the future the author can become a person who helps preserve the character and culture of pesantren inside or outside pesantren.